2015
DOI: 10.1016/j.mam.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Turning the headlights on novel cancer biomarkers: Inspection of mechanics underlying intratumor heterogeneity

Abstract: Although the existence of intratumoral heterogeneity (ITH) in the expression of common biomarkers has been described by pathologists since the late 1890s, we have only recently begun to fathom the staggering extent and near ubiquity of this phenomenon. From the tumor’s perspective, ITH provides a stabilizing diversity that allows for the evolution of aggressive cancer phenotypes. As the weight of the evidence correlating ITH to poor prognosis burgeons, it has become increasingly important to determine the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 89 publications
(133 reference statements)
0
21
0
Order By: Relevance
“…It has been proposed that alterations resulting in genome instability happen early during tumor formation, allowing the accumulation of errors during DNA replication, repair, and chromosome segregation, thereby increasing the likelihood that a cell will acquire multiple genetic changes necessary for tumor progression (4). CIN is possibly the major contributor to intratumoral heterogeneitythat is, the presence of genetically distinct populations of cells within a single tumor that impacts treatment strategy, drug resistance, and tumor evolution (5)(6)(7)(8). For these reasons, defining genes and pathways that drive CIN and understanding the mechanisms that underlie genome stability will contribute not only to an understanding of tumor etiology and progression but will also be relevant for guiding therapeutic strategies.…”
mentioning
confidence: 99%
“…It has been proposed that alterations resulting in genome instability happen early during tumor formation, allowing the accumulation of errors during DNA replication, repair, and chromosome segregation, thereby increasing the likelihood that a cell will acquire multiple genetic changes necessary for tumor progression (4). CIN is possibly the major contributor to intratumoral heterogeneitythat is, the presence of genetically distinct populations of cells within a single tumor that impacts treatment strategy, drug resistance, and tumor evolution (5)(6)(7)(8). For these reasons, defining genes and pathways that drive CIN and understanding the mechanisms that underlie genome stability will contribute not only to an understanding of tumor etiology and progression but will also be relevant for guiding therapeutic strategies.…”
mentioning
confidence: 99%
“…CA, a key driver of CIN and an early driver of intratumoral heterogeneity [32], is associated with tumorigenesis and tumor progression in multiple cancers, including that of the head and neck. Previous studies in surgically resected HNSCCs have shown an association between higher CA and local recurrence, with CA being a better predictor of recurrence than other commonly used parameters such as T stage [33,34]; furthermore, higher CA has been linked with poor overall survival in HNSCCs [35].…”
Section: Discussionmentioning
confidence: 99%
“…Recently for CIN the use of γ-tubulin antibodies has been proposed to detect in tissues centrosome amplification, which could be a possible major cause of CIN in tumors [92]. Centrosome amplification has already been detected in many cancers, such as breast, prostate, pancreatic, colon, and ovarian cancers [93,94].…”
Section: Genomic Instability As a Cause Of Heterogeneitymentioning
confidence: 99%